RELATIONSHIP OF KNOWLEDGE, NUTRITION INTAKE AND OTHER FACTORS RELATED TO THE EVENT OF ANEMIA IN ADOLESCENTS XII CLASS PRINCESS AT KANDANGHAUR VOCATIONAL SCHOOL, 2020 - Mayang Chyntaka; Cucu Nurmala (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2021)
This study aims to determine the relationship between knowledge, nutritional intake and other factors related to the incidence of anemia in XII grade girls at SMK Kandanghaur in 2020. The research method used is a type of survey research using a cross-sectional approach. The population of all female adolescents in grade XII at SMK Kandanghaur is 300 students. Sampling with sampling using random sampling amounted to 75 respondents. The results of the research from the univariate analysis showed that 71 respondents or 94.7% had good knowledge of anemia, 52 respondents or 69.3% with normal nutritional status, 73 respondents or 97.3% with a regular diet, 72 respondents or 96% whose father's job is temporary workers, and 45 respondents or 60% who do not have anemia. Based on the bivariate analysis, it is known that there is no significant relationship between knowledge and the incidence of anemia, there is a significant relationship between nutritional status and the incidence of anemia, there is no significant relationship between diet and the incidence of anemia and there is no significant relationship between father's work and anemia in XII grade girls at SMK Kandanghaur in 2020.